ONE DRAFT OF A POSSIBLE CONSTITUTIONAL ARRANGEMENT FOR KOSOVO AND METOHIJA - Bojan Bojanic; Zaklina Spalevic (Srpska Politička Misao)
The authors will point out some possible models for solving an extremely complex problem, which for decades has been an open issue for which, without much success, a mutually acceptable solution is being sought – Kosovo and Metohija. The paper analyzes three possible options, with different intensity of relations between the Republic of Serbia and so called Kosovo. In the first case, which implies the strongest relationship between Serbia and Kosovo and Metohija, this issue could be resolved by passing a law on substantial autonomy (with changes to certain constitutional provisions) which would formally assign all the competencies now available in the province, while the other two models do not imply the adoption of such a law, so it could be done exclusively by changing the Constitution of the Republic of Serbia. In none of the proposed models, the so-called Kosovo would not have full international legal subjectivity, Serbia would not recognize Kosovo’s self-proclaimed independence, nor could so-called Kosovo become a member of the United Nations, and there would be no Kosovo Army. The province would have internal sovereignty.